ANALISIS KRITIK SOSIAL PADA ANTOLOGI PUISI POTRET PEMBANGUNAN KARYA W.S. RENDRA - Utamie, Zathu Restie; Singgih, Muhammad (LPPM STKIP PGRI Bandar Lampung, 2021)
The problems raised in this study relate to literary criticism in the poem W.S. Rendra. Poetry is one of the right literature to describe the mind of the author, concerning the social life of the community with its various inequalities, as well as one of the media to convey criticism to individuals and groups. The purpose of this research is to keep literary works away from deviant things that endanger the existence of the author. The method used in this study is qualitative method. The data analysis techniques the authors used in this study are : 1)Read Poetry by W.S. Rendra carefully. 2) then write the value of social criticism contained in the poem. 3) Mark supporting sentences containing social criticism. 4) Analyze social criticism based on data obtained. Social criticism contained in the poem by W.S. Rendra entitled Sajak Orang Miskin, Sajak Joki Tobing untuk Widuri, Sajak Seonggok Jagung, Sajak Pertemuan Mahasiswa, and Sajak Sebatang Lisong contains social criticisms that include the related social life faced by society, the social life gaps experienced by students, and the social lives of the rich and poor people.